Vaccination in Patients with Chronic Lymphocytic Leukemia: Current Problems - M. I. Kislova; A. A. Petrenko; M. P. Kostinov; E. A. Nikitin (Эпидемиология и вакцинопрофилактика)
Relevance. Infections are the most common complication of chronic lymphocytic leukemia (CLL). According to registry studies, infections are the cause of death in 10–20% of patients. The emergence of new therapies for CLL has led to a decrease in mortality due to CLL progression, while mortality from infections has remained constant in recent decades.The aim of this literature review is to analyze the effectiveness of vaccine prophylaxis in patients with CLL as well as predictors of vaccine inefficiency according to published data, to explore current guidelines.Conclusions. The mechanisms of immune dysfunction in CLL are complex and associated with both the disease itself and the therapy. Numerous studies have shown that patients with CLL have an inadequate response to most vaccines given routinely in the general population. Vaccination in CLL patients remains a poorly developed topic. Additional clinical trials are needed to improve the effectiveness of vaccination in patients with CLL.